A prompt CNN-FL model based on multi criteria for a smart vertical handoff in heterogeneous system. Issue 4 (18th April 2020) - R, Ganesan; B, Sowmya
Abstract : Purpose: Heterogeneous network is mainly focused to enrich the demands of network's traffic and data rate. Heterogeneous network is an integrated system composed of diverse radio access technologies such as Wi-Fi, UMTS and WiMAX soon. To exchange the packets among these different wireless technologies, an adoptable vertical handoff (VHO) is required. Design/methodology/approach: Various types of techniques have been proposed in line with VHO. However these algorithms lead to the threat of high dropping rate and poor Quality of Service (QoS). We modulate a new methodology by integrating Convolutional Neural Network with Fuzzy Logic (CNN-FL) for an optimum vertical handoff decision process (VHDP). The CNN-FL–based VHDP is very effective because of nonlinearity and generalization capability with uncertain data inputs. Findings: The performance results exhibit that proposed methods show efficient for selecting the appropriate network with maximum throughput. At the same time, the proposed method reduces computational complexity and dropping rate considerably. Originality/value: This paper proposes a novel CNN model along with a FL model for achieving a vertical hand off.